The impact of structural and functional characteristics of social relations as determinants of functional decline - Avlund, Kirsten; Lund, Rikke; Holstein, Bjørn E; Due, Pernille; Sakari-Rantala, Ritva; Heikkinen, Riitta-Liisa (The journals of gerontology. Series B, Psychological sciences and social sciences, 2004)
This study examines whether aspects of social relations at baseline are related to functional decline at 5-year follow-up among nondisabled old men and women. The investigation is based on baseline and follow-up data on 651 nondisabled 75-year-old persons in Jyväskylä (Finland) and Glostrup (Denmark). The analyses are performed separately for men and women. Possible selection problems were considered by using three outcome measures: first, functional decline among the survivors (n = 425); second, functional decline, including death, assuming that death is part of a general decline pattern (n = 565); and third, mortality (n = 651). Social relations were measured at baseline by several items focusing on the structure and function of the social network. In men, no weekly telephone contact was related to functional decline and mortality. Among women, less than weekly telephone contact, no membership in a retirement club, and not sewing for others were significantly related to functional decline and mortality. The associations were stronger when the dead were included in the outcome measure. The results point to the importance of social relations in the prevention of functional decline in older adults.